Students’ Problems in Semantic Meaning Analysis of Literary Works in English Handbooks - Irmawaty Hasyim; Salmia Syarifuddin (Tamaddun Life, 2021)
English handbooks used in High schools fill with literary works. It is either in poem, prose, or drama. These literary works are human’s creatures both in spoken and written language which fills with implicit meaning beneath the stylistic language used in that literary works. Besides, semantics is a branch of linguistics that studies meaning. This study aimed to find out problems faced by students in the analysis of the semantics meaning of literary works found in English handbooks. This study applied the qualitative descriptive method. The result showed that the problems faced by students lied beneath the determination of semantics meanings and their types found in words, phrases, clauses, and sentences in literary works.